Analysis of Market Orientation and Innovation on SMEs Business Performance: Evidence in Kebumen - Susilowati, Ika; Kaharti, Eni (P4M STIE Putra Bangsa, 2020)
This study aims to analyze empirically the influence of customer orientation, competitor orientation, coordination between functions, innovation on business performance in SMEs in Kebumen. The research data was obtained from SME businesses to scientifically test whether customer orientation, competitor orientation, coordination between functions, innovation affects business performance. The sample used in this study were 100 SMEs in Kebumen Regency who had met the established criteria. The analytical method used is multiple linear regression analysis, using the SPSS 21.0 for windows statistical computer program. The results of hypothesis testing in this study indicate that customer orientation and coordination between functions have a positive effect on business performance. Whereas competitor orientation and innovation have no influence on business performance.